ANGKA KEJADIAN LUTS YANG DISEBABKAN OLEH BPH DI RSUP PROF. DR. DR. R. D. KANDOU MANADO PERIODE 2009-2013 - Sampekalo, Gloria; Monoarfa, Richard A.; Salem, Billy (e-CliniC, 2015)
Abstract: Lower urinary tract symptoms (LUTS) often occur among old-aged population. One of the causes of LUTS in aged males is benign prostatic hyperplasia (BPH). Males with severe LUTS will experience decreased libido, difficulty in enducing erection, and decreased sexual satisfaction. This study aimed to find out the number of LUTS occurence, caused by BPH at Prof. Dr. R. D. Kandou Hospital Manado during period 2009-2013. This was a descriptive retrospective sudy using secondary data from the hospital. The results showed that 8 cases (15.1%) in 2009, 16 cases (30.2%) in 2010, 12 cases (22.6%) in 2011, 11 cases (20.8%) in 2012, and 6 cases (11.3%) in 2013. Totally, there were 53 cases during that period of time. The data showed that LUTS caused by BPH most often occured among males aged ≥65 years. Conclusion: In this study, the number of LUTS occurence caused by BPH at Prof. Dr. R. D. Kandou Hospital in 2010 was the highest.Keywords : LUTS, BPHAbstrak: Lower Urinary Tract Symptoms (LUTS) sering terjadi pada populasi usia lanjut. Salah satu penyebab yang paling sering ialah Benign Prostatic Hyperplasia (BPH). Pria dengan LUTS yang berat akan mengalami penurunan libido, kesulitan mempertahankan ereksi dan penurunan tingkat kepuasan seksual. Penelitian ini bertujuan untuk mengetahui angka kejadian LUTS yang disebabkan oleh BPH di RSUP Prof. Dr. R. D. Kandou Manado periode 2009-2013. Penelitian ini bersifat deskriptif retrospektif dengan menggunakan data sekunder dari RSUP Prof. Dr. R. D. Kandou Manado periode 2009 - 2013. Hasil penelitian menunjukkan angka kejadian BPH pada tahun 2009 8 kasus (15,1%), tahun 2010 ditemukan 16 kasus (30,2%), tahun 2011 ditemukan 12 kasus (22,6%), tahun 2012 ditemukan 11 kasus (20,8%) dan tahun 2013 ditemukan 6 kasus (11,3%), dengan total 53 kasus. Penderita LUTS yang disebabkan oleh BPH tersering muncul pada umur ≥65 tahun. Simpulan: Pada penelitian ini angka kejadian LUTS yang disebabkan oleh BPH di RSUP Prof. Dr. R. D. Kandou Manado periode 2009 – 2013, paling tinggi pada tahun 2010.Kata kunci: LUTS, BPH